2014
DOI: 10.4067/s0370-41062014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolismo mineral en niños en diálisis peritoneal crónica

Abstract: The values of FGF23, and PTH are elevated in children with CKD on PD. Klotho levels in CKD patients are lower than control children. A strong association of calcemia with FGF23 and PTH is reported. Residual renal function is inversely associated with FGF23 and Klotho. A high incidence of left ventricular hypertrophy was found evidencing a cardiovascular compromise in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In a previous study of the research team as well as in the patients of this study, FGF23 values in children with CKD on PD were found to be significantly higher than the mean value observed in the control group of healthy children. The Klotho cofactor analysis showed lower values than the control group, and no association with FGF23 or with other biochemical variables studied were found 28 . Sugiura et al, measured the expression of soluble Klotho using an ELISA kit in patients with CKD and in controls, confirming that this protein has decreased levels in uremic patients 29 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous study of the research team as well as in the patients of this study, FGF23 values in children with CKD on PD were found to be significantly higher than the mean value observed in the control group of healthy children. The Klotho cofactor analysis showed lower values than the control group, and no association with FGF23 or with other biochemical variables studied were found 28 . Sugiura et al, measured the expression of soluble Klotho using an ELISA kit in patients with CKD and in controls, confirming that this protein has decreased levels in uremic patients 29 .…”
Section: Discussionmentioning
confidence: 94%
“…FGF23 decreases phosphate reabsorption in the proximal tubule by reducing the expression of sodium-phosphate cotransporter 2a (NaPi-2a) in the apical membrane, generating phosphaturia and suppressing the Cyp27b1 gene encoding 1 a-hydroxylase enzyme, responsible for the second hydroxylation and activation of 25 (OH) vit D3. Igualmente, aumenta la expresión del gen Cyp24 que codifica para 24-hidroxilasa, enzima que inactiva la vitamina D 27,28 . In a previous study of the research team as well as in the patients of this study, FGF23 values in children with CKD on PD were found to be significantly higher than the mean value observed in the control group of healthy children.…”
Section: Discussionmentioning
confidence: 99%